EFEKTIFITAS PROMOSI KESEHATAN TERHADAP PERILAKU IVA TEST PADA WANITA DI WILAYAH PUSKESMAS SUKOHARJO 1 TAHUN 2016 - Fridayanti, Warni; Agustina, Ely Eko (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2017)
Cervicalcancer is a disease with the highest prevalence in women in the world that causes death.Nearly 80% of cervical cancer cases are in developing countries. In Indonesia, 80% -90% of patients with cervical cancer are usually difficult to cure because they come tothe health care with more than 70% are in advanced stage. Lack of knowledge andawareness in women about early detection of cervical cancer is one of the main factors.Health promotion is needed to improve the women’s knowledge to increase the women’sawareness about early detection of cervical cancer. Quasi-experimental study withpretest-posttest randomize design was used. Sample in this study 96 respondents. Thestudy was conducted in October 2016. Data analysis included univariate, bivariate testanalisisis wilcoxon and mann Whitney. Results showed significant differences betweenbefore and after the health promotion using leaflets in behavior (0.005), and there werealso significant differences between before and after health promotion throughmotivation from community leaders in behavior (0.001). There were also significantdifferences between the health promotion using leaflets and the health promotion throughmotivation from community leaders in behavior (0.042).Keyword: Health Promotion, Behavior, IVA test